Peran Posyandu sebagai Pusat Informasi Kesehatan Ibu dan Anak di Desa Suak Puntong Kecamatan Kuala Pesisir Kabupaten Nagan Raya - Aja Maulizar; Agatha Debby Reiza Macella (Journal of Social and Policy Issues, 2022)
This study examines the role of posyandu as a center for maternal and child health information in Suak Puntong Village, Kuala Pesisir District, Nagan Raya Regency. The purpose of this study was to determine the role of posyandu as a health information center and the active role of the community in utilizing posyandu program services as basic health. This study uses an approach approach with data collection techniques through observation, interviews, and documentation. The role of Posyandu in Suak Puntong Village, Kuala Pesisir Subdistrict, Nagan Raya Regency, which is the main target for mothers and children, still needs more innovative health information centers. The problems faced in Suak Puntong Village are due to the lack of awareness of mothers to take their children to the posyandu and a narrow understanding of posyandu activities that are limited to weighing toddlers and other reasons, namely mothers are busy working. Posyandu as a health information center in Suak Puntong Village works as a basic health service as well as a motivator for villagers to improve health quality through its program in the form of an integrated family program. The integrated program provides contributions, weighing children under five, exclusive breastfeeding and complementary feeding, examination of pregnant women, family planning programs, and marginal age couples